Negotiating Linguistic Identities: The Impact of Globalization on English Language Use and Indonesian Identity (Universitas Terbuka, 2024)
Background: Globalization has significantly impacted language use and identity formation worldwide. In Indonesia, the increasing prevalence of English alongside the national language, Bahasa Indonesia, has sparked a complex negotiation of linguistic identities among Indonesians. This research investigates how globalization influences English language use and its implications for Indonesian identity construction in the 21st century. Methods: This qualitative study employed semi-structured interviews with 30 young adult Indonesians from diverse socioeconomic and educational backgrounds. Thematic analysis was used to identify patterns and themes within the interview data, focusing on participants' perceptions of English, its role in their lives, and its impact on their sense of Indonesian identity. Findings: The findings reveal a nuanced understanding of English among young Indonesians. English is perceived as a tool for social mobility, professional advancement, and accessing global knowledge and culture. However, concerns were raised about the potential erosion of Indonesian language and cultural identity due to the dominance of English. Participants expressed a desire to maintain a strong sense of Indonesian identity while also embracing the benefits of English in a globalized world. Conclusion: This study demonstrates the complex interplay between language, identity, and globalization in the Indonesian context. The findings highlight the need for further research on language policies and educational practices that can promote multilingualism and intercultural competence, enabling Indonesians to navigate a globalized world while preserving their unique cultural heritage.